Studi Kebutuhan Fasilitas Ruang Sentra Usaha Mikro, Kecil, dan Menengah Skala Kecil Berbasis Aktivitas Online - Wijanarko, Ghulandito; Dwiyanto, Agung (Nature: National Academic Journal of Architecture, 2024)
Today's massive technological developments have an impact on every aspect of life. The use of technology also has a significant outcome on the business world. The emergence of new business models, such as e-Commerce, illustrates this new business phenomenon. The emergence of e-Commerce in Indonesia provides opportunities for MSMEs to develop and transform their business models into online sales. Despite conducting online marketing, MSMEs have indicated the necessity of infrastructure to facilitate their business activities. This phenomenon created an idea for designing an MSME center that focuses on the business activities of online MSME players. This paper aims to determine the facility needs required by online MSMEs. The research method used is quantitative by collecting data from questionnaire and literature studies and then analyzing these data. This paper reveals that online MSMEs need access to, online marketing space with minimum of 29m2, online warehouse facilities with minimum of 26m2, and banking services to support their business goals.